The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1104/pp.61.6.886
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ethylene Production in Fruit Slices by a Rhizobitoxine Analog and Free Radical Scavengers

Abstract: The rhizobitoxine analog, L-2-amino-4-(2-aminoethoxy)-traas-3-butenoic acid (Ro), wich effectively Iits ethylene productio in apple (Mahus domestca Brkh.) and otber tissues at concentratins at about 68 micromolar, inhibited ethylene productin by about 50 to 70% in green tomato (Lycopersicon esculentum Mill.) Since Lieberman et al. (6) showed that ethylene was derived from carbon atoms 3 and 4 of methionine in apple slices, evidence has accumulated that methionine is the natural precursor of ethylene in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 9 publications
(7 reference statements)
1
53
1
Order By: Relevance
“…Several lines of evidence from both intact tissues and model systems suggest that ethylene formation from ACC may be mediated by free radicals. For example, the reaction can be inhibited in situ by radical scavengers (4,5), is driven by OH in a strictly chemical system consisting of ACC and the components of the Fenton reaction (22), and appears to be facilitated by 02 when catalyzed by isolated microsomal membranes (25). Thus, it is conceivable that bicarbonate might enhance ACCdependent ethylene production by facilitating the formation of these reactive species of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence from both intact tissues and model systems suggest that ethylene formation from ACC may be mediated by free radicals. For example, the reaction can be inhibited in situ by radical scavengers (4,5), is driven by OH in a strictly chemical system consisting of ACC and the components of the Fenton reaction (22), and appears to be facilitated by 02 when catalyzed by isolated microsomal membranes (25). Thus, it is conceivable that bicarbonate might enhance ACCdependent ethylene production by facilitating the formation of these reactive species of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Propyl gallate, which quenches free radicals and thus inhibits ethylene production in higher plants (1) and in the horseradish peroxidase model system (25), was as effective an inhibitor of ethylene evolution as boiling. Chelators which have been shown to inhibit ethylene production from methionine in both the model systems (14,17) and in apple slices (15) also somewhat inhibited ethylene production by the incubating solution.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between these results may be due to a 20-fold difference in concentration of the inhibitors used. Although the effects of rhizobitoxine and its analogue on ethylene production by higher plants are similar (1,16,19), their effects may be different in the fungus and may be related to inhibition of transaminase, which converts a-ketoglutarate to glutamate (21). In shake cultures RO only slightly inhibited the production of ethylene stimulated by methionine (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…LESLIE AND ROMANI Baker et al (2) demonstrated inhibition of ethylene biosynthesis by benzoic acid at concentrations that were also active in this study (Table I), but benzoic acid was considerably less active in pear cells than SA or ASA. This disparity in ability to block ethylene biosynthesis contrasts sharply with observations ofbenzoic acid activity equal to or stronger than that of SA in flower induction (10,26), vegetative growth (12), and disease resistance (27), suggesting different mechanisms may be involved.…”
mentioning
confidence: 94%